Methylene blue induces macroautophagy through 5′ adenosine monophosphate-activated protein kinase pathway to protect neurons from serum deprivation - Xie, Luokun; Li, Wenjun; Winters, Ali; Yuan, Fang; Jin, Kunlin; Yang, Shaohua (Frontiers in Cellular Neuroscience, 2013)
Methylene blue has been shown to be neuroprotective in multiple experimental neurodegenerative disease models. However, the mechanisms underlying the neuroprotective effects have not been fully elucidated. Previous studies have shown that macroautophagy has multiple beneficial roles for maintaining normal cellular homeostasis and that induction of macroautophagy after myocardial ischemia is protective. In the present study we demonstrated that methylene blue could protect HT22 hippocampal cell death induced by serum deprivation, companied by induction of macroautophagy. We also found that methylene blue-mediated neuroprotection was abolished by macroautophagy inhibition. Interestingly, 5′ adenosine monophosphate-activated protein kinase (AMPK) signaling, but not inhibition of mammalian target of rapamycin signaling, was activated at 12 and 24 h after methylene blue treatment in a dose-dependent manner. Methylene blue-induced macroautophagy was blocked by AMPK inhibitor. Consistent with in vitro data, macroautophagy was induced in the cortex and hippocampus of mouse brains treated with methylene blue. Our findings suggest that methylene blue-induced neuroprotection is mediated, at least in part, by macroautophagy though activation of AMPK signaling.